Mythopoeia in Akhavan’s & Eliot’s Poetry - Pourmorad Naseri, Mahin; Ghasemi, Parvin (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2022)
T. S. Eliot, the well-known English poet, and Mehdi Akhavan Sales, one of the pioneers of the Modern Persian Poetry, have applied mythologies in their poetry. The present study is an attempt to make a comparison between Eliot’s early poems, i.e. “The Waste Land” and “The Love Song of J. Alfred Prufrock”, and Akhavan’s two poems, “Qese-e Shahriar-e Shahr-e Sangestan” [The Story of the King of the Stoned City] and “Khan-e Hashtom va Adamak” [The Eighth Task and the Puppet] from a Tolkienian perspective of mythopoeia. Laying their arguments in Jost’s fourth category of comparative studies (themes and motifs), the present authors attempt to depict the similarities and differences in the way the poets approach mythopoeia as a literary technic. In doing so, the mythic figures created by the poets are detected and the characteristics attributed to each are reviewed in the socio-political context of the poets’ life. Then, the philosophical viewpoint implied in creating the myth will be discussed. The findings of the study reveal that while there are similarities in the literary devices and techniques (i.e., imagery, pattern of hero’s journey, …) that the poets have applied, there are differences in terms of poetic language and the kind of myths each poet creates or alludes to. Finally, it will be argued that in applying mythmaking, both poets seem to be warning their fellowmen against the evil life they are involved in. Thus, it is claimed that from a Tolkienian perspective, both poets are mythopoeic both in vision and method.